2003
DOI: 10.1038/sj.jp.7210899
|View full text |Cite
|
Sign up to set email alerts
|

Neonatal Early-onset Group B Streptococcal Disease in the Era of Intrapartum Chemoprophylaxis: Residual Problems

Abstract: OBJECTIVE:To identify limitations of current strategies for intrapartum prophylaxis of neonatal early-onset group B streptococcal infection. METHODS:Retrospective review of infants with culture-proven early-onset group B streptococcal infection admitted to two nurseries and their mothers from July 1992, when ACOG and AAP guidelines for intrapartum prophylaxis were first issued, through December 2001. Information was recorded regarding clinical risk factors for early-onset group B streptococcal infection, colle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
10
0
3

Year Published

2003
2003
2013
2013

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(15 citation statements)
references
References 24 publications
(30 reference statements)
1
10
0
3
Order By: Relevance
“…Inadequate specimen collection and transport from obstetrical clinics to the laboratory could also result in falsenegative results, especially in the presence of light colonization (19,25). The culture method is suspected to lack sensitivity, given that studies of confirmed early neonatal GBS infection have demonstrated disease in neonates born to mothers negative for GBS by culture (15,18), and our results confirm this hypothesis.…”
Section: Discussionsupporting
confidence: 80%
“…Inadequate specimen collection and transport from obstetrical clinics to the laboratory could also result in falsenegative results, especially in the presence of light colonization (19,25). The culture method is suspected to lack sensitivity, given that studies of confirmed early neonatal GBS infection have demonstrated disease in neonates born to mothers negative for GBS by culture (15,18), and our results confirm this hypothesis.…”
Section: Discussionsupporting
confidence: 80%
“…A impossibilidade de encontrar claros fatores de risco levou os autores a concluir que não é possível selecionar, pelos antecedentes, as gestantes que devem receber profilaxia no momento do parto e a recomendar a utilização das culturas pré-natais de triagem. Também Pinto et al 11 não foram capazes de identificar fatores de risco em 46% dos casos de sepse neonatal por EGB.…”
Section: Editorialunclassified
“…3 as well as Pinto et al 4 evaluated the effectiveness of and residual problems associated with the culture-based and risk-based GBS prevention strategies.…”
mentioning
confidence: 99%
“…In Riley's estimation, 50% of those women could have received antibiotics at least 4 hours before delivery. These authors recommended that patient education about GBS screening-culture results and strict attention to maternal GBS culture status upon presentation in labor would improve compliance with antibiotic administration within 4 hours of delivery.Pinto et al 4 reviewed 94 cases of early-onset GBS admitted to two regional level III NICUs from 07/92 through 12/01. Of these infants, 50 (53%) were born to women whose GBS colonization status was (i) unknown and who had no identified risk factors or (ii) whose GBS screening culture was reported as negative.…”
mentioning
confidence: 99%